2019
DOI: 10.1002/rcm.8505
|View full text |Cite
|
Sign up to set email alerts
|

Cell tracking of chromium‐labeled mesenchymal stem cells using laser ablation inductively coupled plasma imaging mass spectrometry

Abstract: Rationale Mesenchymal stem cells (MSCs) are widely used in regenerative medicine research. Evaluating the biodistribution of MSCs is important for determining whether the cells have reached the target tissue, and the time that the stem cells reside in each area is required to estimate the duration of efficacy. Methods A laser ablation inductively coupled plasma imaging mass spectrometry (LAICP‐IMS) method was developed for highly sensitive and quantitative surface analysis of metal elements for solid samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…This could suggest that MSCs do not distribute to other organs after intramuscular injection. This was in line with the findings of similar studies performed following intramuscular injection [62][63][64], with MSCs remaining at the injection site, but without MSCs distributing to organs. However, it has been demonstrated that, despite the lack of distribution of MSCs, when injected intramuscularly in a contralateral muscle to an inflamed area, MSCs are capable of reducing inflammation.…”
Section: Distribution Of Mscs After Intramuscular Injection In Animal Modelssupporting
confidence: 91%
“…This could suggest that MSCs do not distribute to other organs after intramuscular injection. This was in line with the findings of similar studies performed following intramuscular injection [62][63][64], with MSCs remaining at the injection site, but without MSCs distributing to organs. However, it has been demonstrated that, despite the lack of distribution of MSCs, when injected intramuscularly in a contralateral muscle to an inflamed area, MSCs are capable of reducing inflammation.…”
Section: Distribution Of Mscs After Intramuscular Injection In Animal Modelssupporting
confidence: 91%
“…20–30 μm) is approximately five times larger than the narrow pulmonary capillaries ( ca . 5 μm of diameter), when MSCs circulate through the lungs following injections, they most likely will come into contact with surface vasculature, leading to an eventual MSC arrest in the capillaries, followed partially by subsequent extravasation through the vascular wall into the lung tissue. , However, not all Au NPs delivered by the MSCs to the lungs finally penetrated the lung tissue: For the MSC-mediated Au NP delivery, there was a temporal decline in lung accumulation, followed by a temporal increase in liver accumulation, thereby suggesting the translocation of Au NPs initially entrapped within the lungs to the liver. In addition, it must be stressed that MSCs will die over time in the body following intravenous injection, which additionally may have led to the redistribution of Au NPs in the organs as observed.…”
Section: Resultsmentioning
confidence: 99%